Pengaruh QRIS Terhadap Perilaku Impulsive Buying Mahasiswa ditinjau dalam Perspektif Ekonomi Islam - Ahmad, Ahkam; Syahidah Rahmah; Sri Wahyuni (ITB AAS Indonesia Surakarta, 2025)
This study aims to analyze the influence of QRIS digital transactions on the impulsive buying behavior of students at the Faculty of Economics and Business, Universitas Muhammadiyah Makassar, from the perspective of Islamic Economics. The background of this research is based on the growing use of QRIS as a digital payment method on campus and the increasing phenomenon of impulsive buying among students. This research employs a quantitative approach with an explanatory research design. Primary data were collected through questionnaires distributed to 97 respondents who are active QRIS users, using Slovin’s formula for sampling. The data analysis method used is simple linear regression to examine the effect of the independent variable on the dependent variable. The results show that QRIS digital transactions have a significant positive influence on the impulsive buying behavior of students in the Faculty of Economics and Business. Factors such as convenience, practicality, and security are the main reasons for using QRIS; however, they also contribute to impulsive consumption. From the perspective of Islamic Economics, QRIS is considered compliant with Sharia principles as long as it does not involve elements of riba (usury), gharar (uncertainty), or maisir (gambling), but its use should be guided by ethical and spiritual awareness to avoid extravagance. This research is expected to serve as a reference for educational institutions, financial service providers, and relevant stakeholders in improving the quality of Sharia-based digital payment services.